Early physiotherapy care in the frail hospitalised elders: prospective cohort study - Ricci, Emanuela; Marchini, Maria; Lamberti, Gianfranco; Zanlari, Luca; Casati, Vittorio; Freghieri, Camilla; Rusitano, Angela; Ciardi, Gianluca (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Frailty is an age-related condition, of increasing concern given ageing of world population. The aim of this work was the evaluation of early physiotherapy in frail patients admitted at Fiorenzuola d’Arda hospital.       Methods: A prospective cohort study, with two recruitment intervals, was conducted. Patients older than 65 years, with a Barthel Index score of 70 or below, frailty and indication for physiotherapy were recruited. Barthel Index delta, length of hospitalisation, physiotherapy activation time were assessed as main outcome; sub-analyses were conducted according to the cause of hospitalisation. Results: 63 subjects were included in the study, and 5 were later excluded due to complications. Statistical analysis showed significance regarding hospitalisation length (p= 0.03), early activation of physiotherapy (p=0.002), delta Barthel (p=0.03). Sub-analyses showed significance for respiratory patients (p=0.04).Conclusions: Early physiotherapy is effective to address frailty and improve self-efficacy, by enhancing elders’ residual resources. Future studies should integrate field test to deepen motor outcome.